(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the content of the principles used in the organization of training of students of educational institutions to a healthy lifestyle, as well as rational nutrition and physical education in the daily routine, is revealed.